AB0726 Systemic review: agreement between tuberculin skin test (TST) and-gamma release assay (IGRA) blood test for latent tb screening among patients with rheumatic diseases. (23rd January 2014) - Pyo, J.; Sung, Y.-K.
Abstract : Background: The accuracy of screening tests for latent tuberculosis infection (LTBI) such as TST and IGRAs and their agreement are varied according to study. Objectives: We conducted meta-analysis on the positivity of LTBI screening tests and the level of agreement between them in the patients prior to use of anti-TNF agents. Then, we further analyzed the difference in agreement according to underlying rheumatic diseases and the prevalence of TB in each country. Methods: OVID-MEDLINE, EMBASE, and Cochrane Library were searched for LTBI screening in patients with rheumatic diseases, including RA, AS, JIA, and PsA, through Nov 21st 2012. Among 135 literatures retrieved, 18 English original research articles were selected excluding non-FDA approved method, non-rheumatic disease(e.g. IBS, autoimmune diseases), and screenings after TNF-alpha inhibitor use. Heterogeneity was evaluated using the Cochran Q statistic. A random effect model was constructed in STATA 10®. Results: In the pooled analysis, 4764 patients across all rheumatic diseases underwent both TST and one of IGRAs (4334 patients measured by QFT-GIT, and 711 by TSPOT) prior to use of anti-TNF agents. The positivity of TST (>5mm), TSPOT, and QFT-GIT among all patients were estimated as 34.7% [95% CI: 25.7-43.6], 16.1% [7.0-25.1], and 20.7% [14.8-26.6], respectively. The percent agreement between TST and QFT-GIT was 69.8% [64.3-75.3]. In low-to moderate endemic subjects (n=854), positive rate of TST, TSPOT, and QFT-GIT were35.6% [23.3-47.9], 15.5%[10.1-20.8], and 17.5% [9.5-25.5], wherease those of high endemic subjects (n=1010) were 33.6% [24.2-43.0], 23.9% [12.6-38.8], and 30.5% [23.6-37.3], respectively. Percent agreement between TST and QTF-GIT was lower in low-to-moderate endemic area than high endemic area (66.1% [56.5-75.6] vs. 72.7% [65.8-79.6]). In RA subjects (n=1073 patients of 8 studies), the positivity of TST, TSPOT, and QFT-GIT was 31.3% [25.0-37.6], 22.2% [3.0-41.4] and 27.3% [20.1-34.6]. In AS patients (n=317 patients of 3 studies; all high endemics), the positivity of TST, and QFT-GIT was 56.8% [35.0-78.7], and 26.3% [13.5-39.2], and agreement between TST and QFT-GIT was 54.9% [43.9-65.9]. Only sub-analyses by underlying diseases presented non-heterogeneities across literatures measured by Q statistics. Conclusions: Among patients with rheumatic diseases, the screening results of TST and IGRAs are inconsistent across the underlying disease and endemic area. Specifically, a lower level of agreement between TST and IGRAs was found among patients with JIA and AS than RA population. Also, populations originated from low-to-moderate endemic regions, presented more disagreements, mainly due to similar positive rates of TST with lower rates by IGRAs, than patients of high endemic origins. It suggests different strategies are needed for each patient group to detect LTBI in clinical settings considering endemic origins. Disclosure of Interest: None Declared